PEMBUATAN ALAT BANTU UNTUK PROSES Bleeding Air Pada Brake System DI UNIT Dump Truck HD465-7R - Purnomo, Hendro; ,, Rasma; Nasution, Ahmad Yunus (Suara Teknik : Jurnal Ilmiah, 2020)
A dump truck is a medium to long distance carrier where the material carried is loaded by excavators, wheel loaders or shovels. A dump truck is very suitable to be operated in a mining area because of its large load capacity making it very productive. To support dump truck operations, regular maintenance is needed such as general over haul. After completing the general over haul, the next job is the process of bleeding air on the brake system. For bleeding air work in dump truck units, especially HD465-7R, using existing tools is considered ineffective and unsafe so that it can cause problems, namely the release of oil in the form of bursts that can affect the face, especially the eyes and the presence of oil spills that can damage the environment resulting in inefficiency in completion of work. Therefore, it is necessary to make new tools with the aim that the problem can be resolved. The method used is seven up ++ innovation. The results show that the tools made for the process of bleeding air are effective and safe to use so that the oil that comes out is no longer on the face and there are no oil spills that can damage the environment and the completion of work to be efficient.